Predictors of information communication technology integration in ESL teaching among English language lecturers in Malaysian teacher training institutions - Suthagar Narasuman, (2014)
The study is primarily an empirical effort to identify the predictors that determine ICT Integration in teaching English as a second language among faculty members in Malaysian Teacher Training Institutions. The study also examines the English Language lecturers’ current level of ICT integration in TESL teacher training and the varying predictive effect of demographic factors such as age, teaching experience, gender and level of education on ICT integration. The study further examines the significance of the English Language lecturers’ technology proficiency, attitude towards ICT,participation in professional development programmes and ICT infrastructure access and support services in predicting ICT Integration. Finally the study also sought to determine the extent to which the observed variability in ICT integration could be predicted by these factors. The theoretical framework for the study is drawn from a review of the literature on factors that enhance and impede ICT integration. The sample comprises 267 respondents working at the English Language Unit of various teacher training institutions. Survey questionnaires and interviews were used to collect data which was analysed using descriptive statistics, Spearman’s rank order correlation, multiple regression, and reliability analysis. The finding of the study indicate that there is a correlation of 0.241 (R Square) between the dependent variable (faculty ICT integration) and the select group of independent variables. The collective level of significant variance between the dependent variable and the independent variables in the regression model is valued (R2) at 24.1 percent. The findings of the stepwise regression analysis indicate that the independent variables, faculty ICT proficiency, faculty ICT attitude, faculty ICT professional development and faculty ICT access are significant (P < 0.01) predictors that contribute (24.1 percent) towards faculty ICT integration.,However, demographic factors such as age, gender and experience were insignificant predictors. Apart from these, the analysis of the quantitative data and interview transcipts revealed the lack of time, equipment, software applications and context specific professional development programmes as barriers to ICT integration. Lecturers also seemed to lack the necessary skills to integrate content knowledge, pedagogical knowledge and technological knowledge into a seamless instructional technique. The findings imply that these lecturers have the basic skills and right attitude but need to be provided with proper and up-to-date facilities and context specific professional development programmes to further enhance their capacity to integrate ICT in their teaching.